Input–output feedback linearizing control of linear induction motor taking into consideration the end-effects. Part I: Theoretical analysis. (March 2015) - Alonge, Francesco; Cirrincione, Maurizio; Pucci, Marcello; Sferlazza, Antonino
Abstract: This first part of a paper, divided into two parts, deals with the theoretical formulation of the input–output feedback linearization (FL) control technique as to be applied to linear induction motors (LIMs). Linear induction motors, differently from rotating induction motors (RIMs), present other strong non-linearities caused by the so-called dynamic end effects, leading to a space-vector model with time-varying inductance and resistance terms and an additional braking force term. This paper, starting from a dynamic model of the LIM taking into consideration its dynamic end effects, previously developed by the same authors, defines a feedback linearization (FL) technique suited for LIMs, since it inherently considers its end effects. It further emphasizes the role of the LIM dynamic end effects in the LIM control formulation, highlighting the differences with respect to the corresponding technique for RIMs. It describes the control design criteria, taking also into consideration the constraints on the control and controlled variables, arising from the application of such control technique in a real scenario. The second part of this paper describes the set of tests, both in numerical simulations and experiments, performed to assess the correctness of the proposed control technique.